Microdeletions - Angelman syndrome - Marković, Miroslav; Marković, Olivera; Marković, Marija (PONS - medicinski časopis, 2025)
Abstract  The aim of the paper is to show the structural changes in the form of microdeletion malformations and the mechanisms of the origin of these two microdeletion syndromes, especially Angelman syndrome. In addition to the molecular mechanisms of origin, some of the most well-known microdeletion syndromes, their clinical, genetic and phenotypic characteristics are included. In addition to the broader picture of numerous syndromes that arise as a result of microdeletion changes, Angelman and Prader-Willi syndromes are particularly presented. The work refers to findings from the literature that explain the specificities of these syndromes, both in genotype, phenotype and clinical picture, as well as in other aspects of the psychomotor, speech-language and general health course of children and adults. The methods of molecular genetics within prenatal diagnostics are presented as significant preventive measures within the framework of genetic counseling and the prevalence of the occurrence of these all-pervading severe forms of the syndrome. Also, an overview of modern methods and techniques used in differential diagnosis and improving genetic counseling is given. By monitoring significant delays in all modalities of development and problems with general health functioning, some of the types of therapeutic interventions of the holistic and pharmacological-symptomatic type are included. Key words: microdeletion syndromes, Angelman and Prader-Willi syndrome, multidisciplinary approach - prenatal counseling, pharmacological and defectological treatment